Evaluation of Social Media Usage by Dental Practitioners of Pakistan for Professional Purposes – A Cross-Sectional Study - Ghandhi D; Bodani N; Lal A; Maqsood A; Ahmed N; Basha S; Assiry AA; Heboyan A; Karobari MI (Dove Medical Press, 2022)
Dinaz Ghandhi,1 Nikita Bodani,1 Abhishek Lal,1 Afsheen Maqsood,2 Naseer Ahmed,3 Sakeenabi Basha,4 Ali A Assiry,5 Artak Heboyan,6 Mohmed Isaqali Karobari7,8 1Department of Oral and Maxillofacial Surgery, Altamash Institute of Dental Medicine, Karachi, Sindh, Pakistan; 2Department of Oral Pathology, Bahria University Dental College, Karachi, Sindh, Pakistan; 3Department of Prosthodontics, Altamash Institute of Dental Medicine, Karachi, Sindh, 75500, Pakistan; 4Department of Community Dentistry, Faculty of Dentistry, Taif University, Taif, 21944, Saudi Arabia; 5Preventive Dental Science Department, Faculty of Dentistry, Najran University, Najran, 55461, Kingdom of Saudi Arabia; 6Department of Prosthodontics, Faculty of Stomatology, Yerevan State Medical University, Yerevan, 0025, Armenia; 7Department of Restorative Dentistry & Endodontics, Faculty of Dentistry, University of Puthisastra, Phnom Penh, 12211, Cambodia; 8Conservative Dentistry & Endodontics, Saveetha Dental College & Hospitals, Saveetha Institute of Medical and Technical Sciences University, Chennai, Tamil Nadu, 600077, IndiaCorrespondence: Ali A Assiry, Preventive Dental Science Department, Faculty of Dentistry, Najran University, Najran, 55461, Kingdom of Saudi Arabia, Email assirypedo@gmail.com Mohmed Isaqali Karobari, Department of Restorative Dentistry and Endodontics, Faculty of Dentistry, University of Puthisastra, Phnom Penh, 12211, Cambodia, Email dr.isaq@gmail.comBackground: In the past couple of years, the use of social media has been on a tremendous rise with greater attention in the field of healthcare, including dentistry. The use of social media for professional purposes is emphasized as unprofessional use can be detrimental. This study aims to evaluate the use of social media by dentists for professional purposes.Materials and Methods: This cross-sectional study was carried out between December 2021 and March 2022. An online questionnaire was formulated using Google Forms and distributed to the dental professionals through various social media platforms such as Twitter©, Facebook©, Instagram©, Snapchat©, WhatsApp©, and Email©. The questionnaire consisted of two parts: demographic characteristics and questions about the use of social media for professional purposes. For data analysis, SPSS version 25.0 was used, where a multiple linear regression test was used to compare the responses of the participants with their demographic characteristics. A p-value of ≤ 0.05 was considered to be statistically significant.Results: A total of 404 dentists participated in this study with a response rate of 89.7%. The majority of the 276 (68.3%) dentists believed to have a professional account to use social media for professional purposes. Most of the 280 (69.3%) dentists agreed social media improved knowledge and communication skills with the patients. About 248 (61.4%) dentists considered the use of social media for general purposes during clinical hours led to wastage of time. About 160 (39.6%) dentists considered connecting with patients on social media to be inappropriate.Conclusion: The use of social media is on the rise at a tremendous rate in different fields of work, including dentistry. Social media is a great tool for dentists to help expand and grow their clinical practice. However, the professional use and ethics whilst using social media should be considered by the dentists.Keywords: social media, dentists, dental, healthcare, professionalism